An investigation on slope retaining structure in UiTM campuses / Siti Aishah Che Ismail - Che Ismail, Siti Aishah (Faculty of Architecture, Planning and Surveying, 2013)
Retaining structure is widely used in construction to retain the sloping area. They are one of the alternatives to increase the safety level at the sloping area besides to prevent the soil erosion. There are various types of retaining structure. Usually the selection of retaining structure is based on the soil condition. The objective of this academic project is to identify the various types of retaining structure for slope area in UiTM Campuses and to study on the various factors lead to retaining structure failure. Apart from that, this study is carried out to make comparison on retaining structure failure at different case study and to learn on the action taken by the related parties to maintain the retaining structure. This research focuses on the types of slope retaining structure used in UiTM Campuses and there are three case studies was selected to obtain clear understanding about the types and uses of these retaining structure. The data was obtained from interview, questionnaire and on site observation. Interview are focus to the Development and Facility Management Department staff while the questionnaire are distributed to the target group which is pick up randomly from each selected case study and they are from Development and Facility Management Department staff and students. Based on the study, it found that there are various factors that lead to the retaining structure failure. The result is discussed in Chapter Five. It can be said that most of the respondents are aware on the types of retaining structure, the defect and the ground movement at the retaining structure at their campus. Thus, for all of the case study, the condition of the existing retaining structure is safe. This shows that the staff at every maintenance department for all the selected case study is doing their job very well